PENGARUH INTELLECTUAL CAPITAL TERHADAP INDIKASI TERJADINYA FRAUDULENT FINANCIAL STATEMENTS DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Kesehatan dan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2024) - Annisa Yustika Sari; Tarmizi Achmad (Diponegoro Journal of Accounting, 2025)
This study aims to obtain empirical evidence related to the influence of intellectual capital on the indication of fraudulent financial statements with the audit committee as a moderation variable in health industry companies and manufacturing in the consumer goods sector for the period 2019-2024. The sample was selected through purposive sampling as many as 108 observations from 22 companies with a 6-year research period. The research data used is secondary data sourced from the annual report published through the IDX's official website and can be accessed by the Bloomberg terminal. The analysis methods used in this study are logistic regression analysis and moderated regression analysis (MRA) through SPSS 26 application software.The results showed that the human capital component which was partially measured using the amount of employee costs had a negative effect on the indication of fraud in financial statements, the structural capital component measured using the amount of research and development costs had a positive effect on the insignificant, while the relational capital component which measured using marketing costs showed significant negative results on indications of financial statement fraud. Audit committees that are measured only using the number of members doesn’t has a significant influence on the overall influence of the intellectual capital component on the indication of fraudulent financial statements.